Representation and Foreign Policy In The U.S. Press: On The Second Sasun Revolt, Norton Report And Two-Staged Bias - Mehmet Akif Okur; Mustafa Onur Tetik (Yakın Dönem Türkiye Araştırmaları)
One of the important parts of the orientalist “grand narrative” that provides public legitimacy for the intervention of Western states in the internal affairs of the Ottoman Empire is the biased representation of the Armenian revolts in the Western press. The measures taken against the Armenian comitadjis were reported to the Western readers with deliberate and versatile distortions. In this article, an example of how the second Sasun revolt, the most violent period of which was experienced in April-May 1904, was conveyed to the American public will be examined. Thomas H. Norton, the U.S. consul in Harput, prepared a report after traveling around Muş, Sason, Bitlis, and Van to examine the consequences of the second Sasun revolt. A part of this report was served to the press by the US Department of State and newspapers also reported on this issue. The article examines the aforementioned news and the original text of the Norton Report comparatively. The sources in question were evaluated with a deconstructive perspective, and in the context of foreign policy and discourses in the press, the manipulation of the events and their conveyance to the reader were revealed.